Closing the gap: did delivery approaches complementary to home‐based testing reach men with HIV testing services during and after the HPTN 071 (PopART) trial in Zambia?. Issue 1 (9th January 2022) - Phiri, Mwelwa Muleba; Schaap, Ab; Simwinga, Musonda; Hensen, Bernadette; Floyd, Sian; Mulubwa, Chama; Simuyaba, Melvin; Chiti, Bwalya; Bond, Virginia; Shanaube, Kwame; Fidler, Sarah; Hayes, Richard; et al.
Abstract: Introduction: The HPTN 071 (PopART) trial demonstrated that universal HIV testing‐and‐treatment reduced community‐level HIV incidence. Door‐to‐door delivery of HIV testing services (HTS) was one of the main components of the intervention. From an early stage, men were less likely to know their HIV status than women, primarily because they were not home during service delivery. To reach more men, different strategies were implemented during the trial. We present the relative contribution of these strategies to coverage of HTS and the impact of community hubs implemented after completion of the trial among men. Methods: Between 2013 and 2017, three intervention rounds (IRs) of door‐to‐door HTS delivery were conducted in eight PopART communities in Zambia. Additional strategies implemented in parallel, included: community‐wide "Man‐up" campaigns (IR1), smaller HTS campaigns at work/social places (IR2) and revisits to households with the option of HIV self‐testing (HIVST) (IR3). In 2018, community "hubs" offering HTS were implemented for 7 months in all eight communities. Population enumeration data for each round of HTS provided the denominator, allowing for calculation of the proportion of men tested as a result of each strategy during different time periods. Results: By the end of the three IRs, 65–75% of men were reached with HTS, primarily through door‐to‐door service delivery. In IR1 and IR2, "Man‐up" and work/social place campaigns accounted for ∼1 percentage point each and in IR3, revisits with the option of self‐testing for ∼15 percentage points of this total coverage per IR. The yield of newly diagnosed HIV‐positive men ranged from 2.2% for HIVST revisits to 9.9% in work/social places. At community hubs, the majority of visitors accepting services were men (62.8%). In total, we estimated that ∼36% (2.2% tested HIV positive) of men resident but not found at their household during IR3 of PopART accessed HTS provided at the hubs after trial completion. Conclusions: Achieving high coverage of HTS among men requires universal, home‐based service delivery combined with an option of HIVST and delivery of HTS through community‐based hubs. When men are reached, they are willing to test for HIV. Reaching men thus requires implementers to adapt their HTS delivery strategies to meet men's needs. Clinical Trial Number: NCT01900977